Moloekatan Gus Miek: The Concept of Tirakat in Restoring the Purity of Kiai Hamim Djazuli's Teachings - Fuadi, Moh Ashif (Historia Madania: Jurnal Ilmu Sejarah, 2022)
Abstract The Majelis (Assembly) of Sema'an a-Qur'an became a fairly popular tradition in the community by listening to and living the Qur'an 30 Juz. The Majelis Sema'an al-Qur'an Jantiko Mantab and Dzikrul Ghofilin are popularized by Kiai Hamim Djazuli (Gus Miek). This study explains the Moloekatan tradition derived from the Majelis Sema'an al-Quran Jantiko Mantab. Moloekatan, which means following in the footsteps of the holy angel of the coolest of animals in Sema'an al-Qur'an's activities, becomes its uniqueness in the practice of charity. Through socio-historical approaches with observation methods and interviews, this research concluded that the Moloekatan tradition became a derivative-frictions of Majelis Jantiko Mantab activities, which was directly led by one of the sons of the descendants of its founder who was equipped with the concept of riyadhah (tirakat). The form of tirakat in question is puasa (fasting). The jamaah (pilgrims) are encouraged to fast from dawn until the entry of Magrib, but in practice, not all pilgrims can observe fasting and only more emphasize to the khuffadz (memorizers of the Qur'an). The main purpose of the Majelis Sema'an Moloekatan Gus Miek is to restore the blessings of the implementation of Sema'an al-Qur'an and Dzkrul Ghofilin following the teachings of Gus Miek and sanad practice in conjunction with Gus Miek's family. Keyword:Â Sosio-Historical; Moloekatan; Purity; Tirakat